1-[Phenyl(pyridin-2-ylamino)methyl]-2-naphthol - Jie Xiao; Hong Zhao (Acta Crystallographica Section E, 2010)
The title compound, C22H18N2O, was synthesized from naphthalen-2-ol, benzaldehyde and pyridin-2-amine. In the crystal, molecules are linked into centrosymmetric R22(16) dimers by pairs of O—H...N hydrogen bonds. The molecular conformation is stabilized by an N—H...O hydrogen bond. The dihedral angle between the naphthylene ring system and the phenyl ring is 72.86 (12)°.